Metode Safety Stock pada Sistem Jual Beli Perhiasan di UMKM Mutiara Lombok Sirasaga - Aisha Ramadhana Indira Santoso; Agussalim Agussalim; Abdul Rezha Efrat Najaf (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
In developing a business, an inventory management process is needed. Inventory management is the activity of managing inventory items, so that the transaction process in a business remains stable. Safety stock and minimum stock are some examples of methods commonly used for inventory management activities. This method is then applied to a jewelry buying and selling information system, which can calculate the safety stock and minimum stock values for Mutiara Lombok Sirasaga MSMEs. This research aims to digitize the transaction process at Mutiara Lombok Sirasaga MSMEs, as well as helping business owners to know what safe supplies they need to have. The result of this research is a buying and selling information system, which can calculate the safety stock value and minimum stock value for each product. The safety stock and minimum stock values can be used as a reference to simplify the product reorder planning process.